Teacher Ability In Conducting Performance Assessment In Differentiate Learning - Wardani; Rohmadi Mustofa, Dwi; Rosidin, Undang; Sowiyah; Hariri, Hasan (Universitas Pendidikan Ganesha, 2023)
The challenge teachers often face today is evaluating individual student performance. Assessment of student performance is an essential aspect of different learning, but it is difficult for teachers to evaluate individual student performance when there are many students in a class. This study aims to analyze teachers' ability to conduct performance assessments in differentiated learning. The research method used is the mixing method. The population in this study were the teachers of the learning committee at the driving school. The sample consisted of 30 teachers spread across three districts/cities. Data collection techniques using questionnaires, interviews, and documentation. Data analysis techniques using quantitative and qualitative data analysis. The results showed that the teacher's performance appraisal skills in differentiated learning were still very varied and tended to be in choices 2 and 3 in the predetermined rubric. It was concluded that analyzing the teacher's ability to evaluate performance in differentiated learning was still relatively low. Integrating teacher assessment in learning refers to developing, implementing, and analyzing assessment results that are integrated and interrelated in learning programs. Integrating this assessment is very important because it can help teachers monitor student progress, evaluate the effectiveness of learning programs, and make the right decisions in improving learning programs.